Psychopathy and intelligence in high-risk violent women. Issue 3 (4th May 2019) - McKeown, Annette; Thomson, Nicholas D.
ABSTRACT: There has been a longstanding debate and mixed evidence on the link between psychopathy and intelligence. Most of the existing research comes from male prisoners, with the literature on female psychopathy and intelligence remaining sparse. Thus, the current study explored the correlational association between psychopathy and intelligence in a sample of high-risk violent female offenders. This is the first study of its kind from the Offender Personality Disorder (OPD) pathway for women in the United Kingdom (UK). The sample includes high-risk violent women presenting with severe personality disorder. In the present study, we conducted a correlational examination between total scores, and the 2-factor and 4-facet structure of the Psychopathy Checklist-Revised (PCL-R) with intelligence using the Wechsler Adult Intelligence Scale (WAIS). No significant associations were found between total PCL-R scores, or factor 2, and intelligence. Positive associations were found between verbal comprehension and factor 1 and the interpersonal facet. Thus, the results suggest high-risk violent female offenders with interpersonal psychopathic traits demonstrate higher levels of verbal comprehension skills. This finding may help explain why psychopathic female offenders, who can be characterized by deceitful and egocentric behaviours, may be able to successfully charm and con others for their own personal gain.